Performing Finance: The Industry, the Media and Its Image. - Clark, G; Thrift, N; Tickell, A (2004)
Much of the academic finance literature has been devoted to theoretical principles concerning portfolio design, the efficient market and strategic asset allocation. Similarly, industry organization studies have been concerned with the fundamentals of firm structure, entry and exit from the industry, and spatial and industrial concentration. But finance is also a never-ending series of daily stories, issuing from the pink pages of respectable broadsheet newspapers and other print media and increasingly dominated by the cacophony of voices, images and events broadcast by television and on-line real-time data services. Finance has become a media event, with its breathless reporters and star anchorpersons more often approximating Entertainment Tonight or even (at the limit) MTV. This fact of financial life could be treated as ephemeral and of minor significance (compared to the "real" facts of economic principles). But financial institutions take it very seriously indeed. How and why this is the case are the topics of this paper. Drawing upon recent studies of the industry and media, as well as our own studies of the industry and its decision-making protocols, we sketch the elements of finance as entertainment. We emphasize the format and content of morning shows such as those broadcast on CNBC as well as the implications of programmes like these for the trading strategies of major financial conglomerates. The paper closes with comments on the implied research agenda.